Social pathways from the HIV/AIDS deadlock of disease, denial and desperation in rural Malawi - Bryceson, Deborah Fahy; Fonseca, Jodie; Kadzandira, John (International Food Policy Research Institute, 2006)
For the past 20 years, AIDS in Sub-Saharan Africa has been considered a disease of high mobility largely associated with political strife1 or urbanization.2 With its largely peaceful recent history and heavily rural population, however, Malawi poses several challenges to existing assumptions about this demographic and social profile of the disease. Adult HIV prevalence in the country was estimated at 14.1 per cent in 2005, among the highest in the world. More than half a million Malawians have died of AIDS to date in a country of approximately 11 million people.